Diagnostic approach to localised organising pneumonia: A case report - Đurić Mirna; Považan Đorđe; Đurić Dejan; Eri Živka; Trudić Anika (Vojnosanitetski Pregled)
Introduction. Localised organising pneumonia, radiologically presented with oval or round shadows mimicing lung cancer or metastases, is a major issue in differential diagnosis. Case report. A female patient was hospitalized to clarified the etiology of multiple nodular lung lesions. The chest X-ray and the chest computed tomography (CT) revealed bilateral patchy and nodular shadows, and round lung lesions, respectively. Neither sputum analyses, nor histology of bronchoscopy samples clarified the etiology of these lung lesions. As secondary deposits in the lungs were suspected, video-assisted thoracoscopy and anterolateral right minithoracotomy with atypical upper and lower lobe resection were performed. The frozen-section analysis suggested the benign nature of the lesion, and the definite histopathological finding of localised organising pneumonia was established. Due to bilateral lung lesions, corticosteroids were applied. Seven weeks later, the chest CT finding revealed a total regression of the lesions. Conclusion. A surgical resection was necessary to diagnose the localised organising pneumonia which mimiced secondary malignant lesions, thus establishing the definite etiology of lung lesions. Bronchoscopic cryobiopsy, recently introduced in order to obtain peripheral lung biopsy samples, has provided new possibilities in the diagnosis and treatment of neoplastic and non-neoplastic lung diseases.